Rasgo De Personalidad y Psicopatología En Mujeres Transgénero Consumidoras de Marihuana En la Ciudad de Ibagué (2023)
The body becomes a tool of political control from birth, shaped by androcentric norms that mold and impact daily life through the adaptation to gender expectations. This impact is particularly noticeable in female bodies.